PENGUATAN RELATIONSHIP CAPITAL PADA PELAKU IKM INDUSTRI TENUN DI KABUPATEN DONGGALA - Asngadi, Asngadi; Nurdin, Djayani; Kasim, Muh. Yunus; Husnah, Husnah; Nugraha, Mohammad Ega; Palawa, Muhammad Riswandi (Batara Wisnu : Indonesian Journal of Community Services, 2021)
One challenge for the development of SMEs is the lack of access to financial institutions and markets, so it is difficult for SMEs to develop. Difficult access to financial resources will impact the limitations of business expansion which has an impact on the weakness to expand business volume. On the other hand, weak market access also impacts the small size of the market controlled by IKM, which impacts the slight growth in product demand. The weakness factor attached to IKM is the direct access to business development. This service program is intended to provide knowledge on how to manage relational capital for IKM businesses so that they will be able to grow in the long term. Especially for IKM weaving in Towale village, a tourist village being developed by the Dongggala Regency government. Implementation time is one month. With research outputs in the form of articles published in devotional journals, banned and activity videos